Non-clinical demands are pushing experienced UK surgeons out of the NHS†. (2nd July 2016) - Walker, A.; Awad, Z.; Tolley, N.; Narula, A.; Bradley, P.
Abstract: Introduction : Early retirement of surgeons represents lost assets to a health service. The validated retirement decision inventory (RDI) 'Push Pull Anti-Push Anti-Pull' characterizes why and when individuals enter retirement, using four subscales to balance the perceived benefits and costs of continuing to work versus those of retirement. We used this RDI to examine what influences surgeons to retire from the UK health service. Material and methods : A 16-item self-report questionnaire was distributed to UK surgical consultants, examining the four domains of practice: clinical knowledge, judgement, technical skills, and professional/personal demands. Four subscales of pros and cons of work and retirement were rated on a Likert-type scale in each domain. Item scoring then derived a score for each subscale and domain. Results : A total of 141 participants completed the survey: 81% were currently employed in and 19% were retired from regular practice. Professional/personal demands consistently scored as the dominant domain: it was rated as significant in pushing surgeons out of work and failed to provide benefit to continue working. Relinquishing these demands was a significant attraction to retirement without any perceived cost. Conclusions : Non-clinical demands are a key to surgeon exit from the UK health service – it pushes them out and makes it attractive to enter retirement. By contrast, knowledge, judgement, and operative factors all made surgeons content to continue working and were not a pressure to leave practice. We would recommend a debate on how to mitigate non-clinical pressures on experienced surgeons to prolong their careers.